2020
DOI: 10.1038/s41467-020-16718-3
|View full text |Cite
|
Sign up to set email alerts
|

MCM8IP activates the MCM8-9 helicase to promote DNA synthesis and homologous recombination upon DNA damage

Abstract: Homologous recombination (HR) mediates the error-free repair of DNA double-strand breaks to maintain genomic stability. Here we characterize C17orf53/MCM8IP, an OB-fold containing protein that binds ssDNA, as a DNA repair factor involved in HR. MCM8IPdeficient cells exhibit HR defects, especially in long-tract gene conversion, occurring downstream of RAD51 loading, consistent with a role for MCM8IP in HR-dependent DNA synthesis. Moreover, loss of MCM8IP confers cellular sensitivity to crosslinking agents and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(101 citation statements)
references
References 81 publications
3
78
0
Order By: Relevance
“…1e). Indeed, the gel quantification revealed a statistically significant increase (p=0.02 using a two-tailed Student's t-test 24 , see Supplementary Fig. S1a and Supplementary Table S2 for all the plotted data) of the percentage of ds product formed after incubation (0.5 to 40 min) with CSB (24.6%) compared to the control without the protein (8%), but the G4 resolution remains partial and, most importantly, does not increase with increasing incubation times (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1e). Indeed, the gel quantification revealed a statistically significant increase (p=0.02 using a two-tailed Student's t-test 24 , see Supplementary Fig. S1a and Supplementary Table S2 for all the plotted data) of the percentage of ds product formed after incubation (0.5 to 40 min) with CSB (24.6%) compared to the control without the protein (8%), but the G4 resolution remains partial and, most importantly, does not increase with increasing incubation times (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We prioritized genes by an overall APOBEC essentiality score: average log2 fold-change (LFC) over six measurements: three time points for the A549 TP53-/- cell line (T9, T12 and T15) and three for the LXF-289 cell line (T5, T10 and T15). The top five hits by this score were the genes coding for the AP-site protecting protein HMCES[42], the RAD9A cell cycle checkpoint control protein, the MCM8 component of the MCM8-MCM9-HROB complex[37,38,53], ATXN7L3, a component of the SAGA chromatin modifying complex[54,55], and HGC6.3, an uncharacterized protein. For four of the five genes, the individual gRNAs, four per gene, consistently sensitized cells to A3A expression (Fig 2B and S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, nucleotide excision repair (NER) and DNA mismatch repair (MMR) were enriched in both cell lines, as well as the regulation of the cell cycle (Fig 2D and S3 Table). In LXF-289 cells, the non-homologous end-joining (NHEJ) and Fanconi anemia pathways were strongly represented among the top hits enriched, as well as MCM8, MCM9 and HROB, genes that have previously been implicated in HR (Fig 2D and S3 Table)[37,38,53]. Further enriched pathways related to DNA repair included error-prone TLS and telomere maintenance in LXF-289 cells.…”
Section: Resultsmentioning
confidence: 99%
“…We prioritized genes by an overall APOBEC essentiality score: average log 2 fold change (LFC) over 6 measurements: 3 time points for the A549 TP53−/− cell line (T9, T12, and T15) and 3 for the LXF-289 cell line (T5, T10, and T15). The top 5 hits by this score were the genes coding for the AP site protecting protein HMCES [42], the RAD9A cell cycle checkpoint control protein, the MCM8 component of the MCM8-MCM9-HROB complex [37,38,55], ATXN7L3, a component of the SAGA chromatin modifying complex [56,57] Next highest-ranking hits included the UBA6 ubiquitin-activating enzyme and a further 5 genes that were all related to DNA repair, DNA replication, or cell cycle control (DDX11, MCM9, CDC23, MAD2L2 (also known as REV7), and HROB (also known as C17ORF53 or MCM8IP); S1 Table ).…”
Section: Crispr/cas-9 Genetic Screen For A3a Synthetic Lethalitymentioning
confidence: 99%
“…We performed a CRISPR/Cas-9-based genome-wide screen for genes required to tolerate A3A-mediated DNA damage in a panel of cell lines from non-small cell lung cancer (NSCLC), where APOBEC activity has been shown to play an important role in tumor evolution [3,4,[34][35][36]. Among other hits, we identified factors involved in multiple DSB repair pathways, including RAD9A, a component of the 9-1-1 alternative clamp loader and the recently characterized MCM8-MCM9-HROB complex [37][38][39][40]. Crucially, we found that different genetic backgrounds are consistently and strongly dependent on the gene encoding HMCES (5hmC binding, embryonic stem cell-specific protein) for cell viability [8,15] under APOBEC stress, but not otherwise.…”
Section: Introductionmentioning
confidence: 99%